MO960: Sarcopenia: An Overlooked Diagnosis in Kidney Transplant Recipients. (3rd May 2022) - Gül Özcan, Şeyda; Sonmez, Ozge; Akman, Zafer; Karaca, Cebrail; Atli, Zeynep; Trabulus, Sinan; Seyahi, Nurhan
Abstract: BACKGROUND AND AIMS: Sarcopenia is characterized by an involuntary loss of skeletal muscle mass, strength, and function and is usually associated with older age. However, sarcopenia may also be seen at younger ages in patients with chronic kidney disease. The European Working Group on Sarcopenia in Older People (EWGSOP) recently proposed a standardized definition of sarcopenia. We aimed to investigate the incidence of sarcopenia and associated factors in renal transplant recipients. METHOD: We examined consecutive adult (age >18 years) renal transplant recipients under regular follow-up in our outpatient clinic during December 2021. We assessed the muscle strength with a handgrip test using a dynamometer and with a chair stand test. Using the Sergi formula, we used bioimpedance analysis to estimate the appendicular skeletal mass. Finally, we measured the gait speed to assess physical performance. Probable sarcopenia was defined as the presence of low muscle strength. Following that, sarcopenia was diagnosed with low muscle quantity in patients with probable sarcopenia according to the revised criteria by the EWGSOP. We retrieved the clinical and laboratory data from the patients' medical records. RESULTS: We recruited a total of 93 kidney transplant recipients (mean age: 59 ± 1.4, male gender 58.1%). About 15.0% of the patients were cadaveric transplants. Probable sarcopenia was found in 31 patients (33.3%), of which 14 (15.0%) were diagnosed with sarcopenia. Diabetes mellitus and lower albumin levels were the significant factors associated with the presence of probable sarcopenia (P = 0.01, P = 0.015, respectively; Table 1 ). On the other hand, sarcopenia was significantly associated with cadaveric transplantation (P = 0.02; Table 2 ). CONCLUSION: We found that probable sarcopenia and sarcopenia were highly prevalent in our relatively young renal transplant recipients. We recommend active screening for the presence of sarcopenia in renal transplant recipients, especially in the cadaveric ones.